Delayed enhancement imaging in a contemporary patient cohort following correction of tetralogy of Fallot. (10th November 2014) - Preim, Uta; Sommer, Philipp; Hoffmann, Janine; Kehrmann, Jana; Lehmkuhl, Lukas; Daehnert, Ingo; Gutberlet, Matthias; Grothoff, Matthias
Abstract Objective To test the hypothesis that myocardial scars after repair of tetralogy of Fallot are related to impaired cardiac function and adverse clinical outcome. Methods A total of 53 patients were retrospectively analysed after repair of tetralogy of Fallot. The median patient age was 20 years (range 2–48). Cardiac MRI with a 1.5 T magnet included cine sequences to obtain volumes and function, phase-sensitive inversion recovery delayed enhancement imaging to detect myocardial scars, and flow measurements to determine pulmonary regurgitation fraction. In addition, clinical parameters were obtained. Results An overall 83% of patients were in NYHA class I. All patients with the exception of 2 (96%) had pulmonary insufficiency. Mean ejection fraction and end-diastolic volume index were 46% and 128 ml/m2 for the right ventricle and 54% and 82 ml/m2 for the left ventricle, respectively. Excluding enhancement of the septal insertion and prosthetic patches, delayed enhancement was seen in 11/53 cases (21%). Delayed enhancement of the right ventricle was detected in 6/53 patients (11%) and of the left ventricle in 5/53 patients (9%). The patient group with delayed enhancement was significantly older (p=0.003), had later repair (p=0.007), and higher left ventricular myocardial mass index (p=0.009) compared with the group without delayed enhancement. Conclusions This study reveals that scarring is common in patients after surgical repair of tetralogy of Fallot and is associated with older age and late repair. However, there was no difference in right ventricular function, NYHA class, or occurrence of clinically relevant arrhythmias between patients with and those without myocardial scars.